„Pociesz i mię tu na chwilę…” Problematyka religijna Pieśni Nikodema Muśnickiego SJ - Janiec, Adam (Wydawnictwo Uniwersytetu Rzeszowskiego, 2016)
The article presents the most important religious themes in "Pieśni" ["Songs"] by Nikodem Muśnicki, a Jesuit from Polotsk, who was active during the Enlightenment. His biography, as presented in the introductory section, places him among forgotten writers, representatives of classicism after King Stanislaus II, and is a starting point in the interpretation of his songs. The analysis of selected pieces, published in the volume "Drobniejsze poetyckie zabawki" ["Smaller Poetic Toys"] and those which remained in manuscript, clearly indicates that Muśnicki chose the most important religious problems as his object of poetic reflection. He is interested in God, man and the world. Within these themes he also analyses more detailed issues: the essence of the Supreme Being, the existential situation of the human being, the place of man in the universe, and, last but not least, relations of God and man. The poet’s works are an interesting example of Polish religious poetry during the Enlightenment.
“Comfort me here for a moment…”: Religious Themes in Pieśni by Nikodem Muśnicki SJ
Keywords: motywy religijne; poezja oświecenia; jezuici; Nikodem Muśnicki; Opatrzność; oda; Bogurodzica; religious motives; Enlightenment poetry; Jesuits; Nikodem Muśnicki; Providence; ode; “Bogurodzica” [“Mother of God”]